Seberapa Jauh Aku Bisa Bangkit? Sebuah Studi Mengenai Profil Resiliensi Psikologis Remaja Panti Asuhan - Bellatrix Dwi Rachmawati; Ratih Arruum Listiyandini; Rina Rahmatika (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2019)
The purpose of this research is to describe the profile and level of psychological resilience of adolescents living at social shelter.  This research is using quantitative, cross-sectional design, descriptive approach and the population is adolescents who live at social shelter in Jakarta and Bekasi. Due to the explorative nature of this study and lack of the acurate data about total amount the teenagers, the sample of this research is taken by using convenience sampling technique across 12 Social Shelter in Jakarta and Bekasi. The sample of the study is 200 Adolescents. Adapted scale of resilience by Connor – Davidson was used for measure resilience level and descriptive statistic was used for the analysis. The result of this research found that 46.5% of participants have high resilience and 52.5% has moderate level of resilience. Whereas, only 1% who has low level of resiliences. Based on the analysis from each dimension, the highest dimension of resilience is in the domain of “Personal Competence” and the lowest one is on “Tolerance of Negative Affect”. This result implied that to developing resilience program for adolescents at social shelter, it is needed to help them develop their ability to overcome the negative affect.